field Salem, 2018 - Gush, Simon (Kronos: Southern African Histories, 2022)
Simon Gush is an artist and filmmaker living in Johannesburg. His work examines work, labour and land. He completed a postgraduate certificate at the Hoger Instituut Voor Schone Kunst, Ghent and a MA Sociology), University of the Witwatersrand and is currently a PhD (History) candidate at Rhodes University.